2018
DOI: 10.1097/igc.0000000000001352
|View full text |Cite
|
Sign up to set email alerts
|

Atl

Abstract: ObjectivesCisplatin and mitomycin C exert high activity towards BRCA1-deficient cells. This study aimed to evaluate the efficacy of a combination of these drugs in hereditary BRCA1-associated ovarian cancer (OC).MethodsTwelve OC patients, who could not be treated by primary debulking surgery owing to extensive tumor spread, were given neoadjuvant cisplatin (100 mg/m2) and mitomycin C (10 mg/m2) every 4 weeks for 3 (n = 9), 2 (n = 2), or 4 (n = 1) cycles.ResultsThe decrease of tumor burden and complete surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with other reports that BRCA mutation status alone does not unequivocally determine platinum chemotherapy response. Similar to Gorodnova and colleagues ( 44 ), we found that patients with BRCA mutations had longer survival and about 40% of these patients achieved a pCR ( 44–46 ). Within the discovery cohort, 44% ( n = 4) of tumors with BRCA mutations were scored as RAD51-High, and these patients all had poor responses to platinum chemotherapy and decreased survival.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with other reports that BRCA mutation status alone does not unequivocally determine platinum chemotherapy response. Similar to Gorodnova and colleagues ( 44 ), we found that patients with BRCA mutations had longer survival and about 40% of these patients achieved a pCR ( 44–46 ). Within the discovery cohort, 44% ( n = 4) of tumors with BRCA mutations were scored as RAD51-High, and these patients all had poor responses to platinum chemotherapy and decreased survival.…”
Section: Discussionsupporting
confidence: 88%
“…Neoadjuvant combination of cisplatin and mitomycin C resulted in complete pathological responses, i.e. in the elimination of all detectable cancer cells, in some BRCA1/2-driven OCs[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1-driven cancers are particularly sensitive to systemic platinum-based treatment; hence, this category of OC is usually amenable to complete surgical debulking. Despite that presumably efficient platinum-based therapy is administered again after the surgery, it apparently cannot eliminate the residual cancer cells, given that almost all OC treated by this scheme eventually relapse[ 44 ].…”
Section: Selection Of Pre-existing Brca1-proficient Cells During Platinum-based Therapymentioning
confidence: 99%